Maintenance of Minute Circulation Volume during Orthotopic Liver Transplantation - D. A. Levit; E. A. Chvanov; Yu. I. Petrishchev; A. L. Levit (Общая реаниматология, 2011)
Objective: to optimize procedures to maintain minute circulation volume at different stages of orthotopic liver transplantation. Subjects and methods. In the period 2005—2010, Sverdlovsk Regional Clinical Hospital One performed 32 orthotopic liver transplantations, including one retransplantation. The patients’ ASA class was (4—5). The operations were carried out under general anesthesia. The mean duration of surgery was 8.1 (range 5.8—10.5) hours. The investigators applied anesthesia based on iso-fluorane 0.6—0.9 MAC (by monitoring the anesthesia depth index with cerebral state index (CSI-40-60)), as well as extended central hemodynamic monitoring (prepulmonary hemodilution). All the operations were made via portofemoroaxillary bypass, by using a centrifugal Biopump. Eight surgical stages were identified: 1) run-in (after tracheal intubation); 2) liver mobilization; 3) partial bypass; 4) complete bypass (hepatectomy, a liver-free period); 5) reperfusion; 6) a postreperfusion period (bypass end); 7) biliary repair; 8) the end of an operation. The concentrations of blood parameters, electrolytes, acid-base balance, and the levels of lactate and glucose were examined. The data were processed statistically. Central hemodynamics was monitored by prepulmonary thermodilution, by calculating cardiac index (CI), stroke index, and total peripheral vascular resistance index (TPVRI) at the stages: liver mobilization, postreperfusion period (bypass end), and the end of surgery. Results. Even during partial bypass, there was a significant drop in mean blood pressure (MBP) as compared to the baseline levels (p<0.05). Reperfusion was also accompanied by a significant decrease in MBP and an increase in heart rate. At the end of reperfusion and in the postreperfusion period, TPVRI was halved (689.2±68.0) as compared to the baseline levels. In the postreperfusion period, central venous and pulmonary artery pressures were significantly increased by 32 and 21%, respectively. That period was marked by a significant rise in CI. Serum lactate and glucose elevations starting from the complete bypass stage were associated with the liver being excluded from the circulation and cannot be a marker of inadequate tissue perfusion. Conclusion. The decrease in MBP during portofemoroaxillary bypass is associated with hypovolemia and mainly with vasoplegia during reperfusion. Approaches to maintaining the adequate minute circulation volume depend on the surgical stage: sufficient preload is needed during complete bypass and it is expedient to combine an infused load with vasopressors for the correction of the reperfusion syndrome with low TPVR. Key words: liver transplantation, minute circulation volume, general anesthesia, central hemodynamics.